2017
DOI: 10.1111/gcb.13701
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of bloom‐forming and perennial seaweeds to elevated pCO2 conserved across levels of environmental complexity

Abstract: Macroalgae contribute approximately 15% of the primary productivity in coastal marine ecosystems, fix up to 27.4 Tg of carbon per year, and provide important structural components for life in coastal waters. Despite this ecological and commercial importance, direct measurements and comparisons of the short-term responses to elevated pCO in seaweeds with different life-history strategies are scarce. Here, we cultured several seaweed species (bloom forming/nonbloom forming/perennial/annual) in the laboratory, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
(88 reference statements)
0
12
0
Order By: Relevance
“…We assumed the high stocking density conditions of aquaculture farm to find realistic growth of G. lemaneiformis. In addition, Xu et al (2017a) found that the RGRs of short-time cultivation period were higher than those of long-time cultivation time. They explained that decreased of RGRs resulted from the acclimation to culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed the high stocking density conditions of aquaculture farm to find realistic growth of G. lemaneiformis. In addition, Xu et al (2017a) found that the RGRs of short-time cultivation period were higher than those of long-time cultivation time. They explained that decreased of RGRs resulted from the acclimation to culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al . found that ephemeral species of the genus Ulva could increase their photosynthesis and growth rates under elevated CO 2 conditions, while longer‐living perennial species showed smaller responses. In order to protect themselves from the damage caused by UV radiation, macroalgae can utilize escape, repair and barrier mechanisms to protect them during the process of adaptation and evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Although LOX products have been described from Phaeophyceae, to the best of our knowledge, there has been no comprehensive study of LOX genes in brown algae available up to now, and their phylogenetic relationships with LOXs of other phyla remain poorly understood. Brown macroalgae are the dominant vegetation in many benthic marine habitats with high ecological and economic significance ( Xu et al, 2017 ). Particularly, Saccharina japonica is one of the most economically important seaweed in marine aquaculture.…”
Section: Introductionmentioning
confidence: 99%